Analisa Pengembangan SIMAK UNKRIS Terhadap Proses Penilaian Mahasiswa dengan Metode Analytical Hierarchy Process (AHP) - Harjono P. Putro; , Herwanto (https://journal.teknikunkris.ac.id/index.php/JMTR, 2022)
The presence of the development of information and communication technology in the field of education has an impact on effective learning and directly involves active students in learning. Krisnadwipayana University (UNKRIS) is one of the universities in Jakarta that also uses the campus academic information system (SIMAK) which has been used and developed by itself since 2017 until now. One of the features of listening is a feature where this feature is used by lecturers who teach at UNKRIS, especially the Faculty of Engineering who actively uses SIMAK. In the information system there are still several parameters that can be improved including functionality, appearance, quality of service, navigation, and usability. So to find out how the satisfaction level of SIMAK users at Krisnadwipayana University uses the Analytical Hieracy Process method to make decisions in solving problems in priority setting.